ASSESSING THE MODERATING ROLE OF EDUCATIONAL QUALIFICATION IN JOB SATISFACTION AND TURNOVER INTENTION RELATIONSHIP OF BASIC SCHOOL TEACHERS: EVIDENCE FROM NORTHERN GHANA - Abukari, A. K.; Alhassan, I. (UDS International Journal of Development, 2021)
The emphasis on the Educational Qualifications (EQ) of employees, the demand for skilled labour and the professionalization of the occupational structure of teachers in general, have created a dilemma for employers and school authorities in retaining their competent and experienced staff and meeting their job needs on one hand, and increasing pressure to release them for higher edu-cational experience on the other. This paper examines the moderating role of teachers’ EQ in their Job Satisfaction (JS) and Turnover Intention (ToI) relationship in the Tamale Metropolis of the Northern Region of Ghana. The proposed model was evaluated based on valid data from 116 teachers obtained from a cross-sectional survey. To confirm whether EQ will moderate the JS and ToI relationship, a process macro (Hayes, 2018 v. 3.4) was run with mean cantering and 5000 bootstrapping. Regression Analysis was employed to determine the relationships proposed in the study. The results show a significant but inverse relationship between JS and ToI of teachers in the Metropolis. However, the EQ moderator function in JS and the ToI relationship was not support-ed. It was also found that the Teachers’ EQ had no significant effect on their ToI in the Metropolis. Empirically, the study extends our understanding of the constructs discussed. The paper also dis-cusses some managerial implications, and because there were some contextual limitations, direc-tions are also provided for future studies.